Can Holistic Empowerment and Digital Platform Arouse Creative Economy Innovation? - Anjaningrum, Widiya Dewi; Moko, Wahdiyat (Department of Management, Faculty of Economics and Business, Brawijaya University, 2023)
Although many studies investigated the relationship between digital platform capabilities and innovation performance, finding research that simultaneously links the two constructs to holistic empowerment and innovation still needs to be completed. This study examined the relationship between Creative Industry Holistic Empowerment and Digital Platform Capability, Holistic Innovation Capability, and Innovation Performance through a questionnaire survey of 260 creative entrepreneurs in East Java. The results of the PLS-SEM high-level analysis show that the Holistic Empowerment of Creative Industries has a strong impact on digital platform capabilities, and there is a strong partial mediating role of holistic innovation capabilities on the effect of digital platform capabilities on innovation performance. So, it is important for every creative Industry to holistically empower its resources in order to be able to master digital platforms, which ultimately have an impact on innovation and performance. Subsequent research is directed at directly relating the holistic empowerment of the creative Industry to innovation and performance, as well as focusing research subjects on one of the creative economy sub-sectors so that the benefits from research are more striking.